HAPPY NEW YEAR (Tufts Archival Research Center, 2007)
Advertisement opposing an increase in New York cigarette taxes. Questions the stability of cigarette taxes as a source of revenue. Accuses tax increase of being unfair. Urges citizens to call their legislators and express opposition to the tax raise.